Integrating Concepts of Physiological and Behavioral Resistance to Parasites - Amoroso, Caroline R. (Frontiers in Ecology and Evolution, 2021)
Conceptual parallels between physiological and behavioral forms of resistance to parasites have led to the development of terminology like “the behavioral immune system” to refer to behaviors that combat parasites. I extend this metaphor by applying findings from research on physiological resistance to generate predictions for the ecology and evolution of behavioral resistance (here, synonymous with avoidance). In certain cases, behavioral resistance may follow similar evolutionary dynamics to physiological resistance. However, more research on the nature of the costs of behavioral resistance is needed, including how parasite transmission mode may be a key determinant of these costs. In addition, “acquiring” behavioral resistance may require specific mechanisms separate from classical forms of conditioning, due to constraints on timing of host learning processes and parasite incubation periods. Given existing literature, behavioral resistance to infectious disease seems more likely to be innate than acquired within the lifetime of an individual, raising new questions about how individual experience could shape anti-parasite behaviors. This review provides a framework for using existing literature on physiological resistance to generate predictions for behavioral resistance, and highlights several important directions for future research based on this comparison.